Greece : Fifth Review Under the Extended Arrangement Under the Extended Fund Facility, and Request for Waiver of Nonobservance of Performance Criterion and Rephasing of Access. (IMF Staff Country Reports; Country Report ;, 2014)
This paper discusses Greece's Fifth Review Under the Extended Arrangement Under the Extended Fund Facility (EFF), and Request for Waiver of Nonobservance of Performance Criterion and Rephasing of Access. Greece has gone from having the weakest to the strongest cyclically adjusted fiscal position within the euro area in just four years. But more fiscal adjustment is needed to restore debt sustainability. Structural reforms are progressing, although unevenly. The redoubling of efforts to liberalize products and service markets are much welcomed. On the basis of reforms undertaken in the context of this review, and the government's policy commitments going forward, the IMF staff supports the completion of the fifth review.